Laser modification method of transparent ceramic and transparent ceramic
Through the combination of laser pretreatment and laser impact enhancement, the problem of improving optical and mechanical properties of transparent ceramics is solved, and the comprehensive performance improvement of materials is achieved. It is suitable for high-performance optical components and high-power laser systems.
Patent Information
- Application Number
- CN202411309091.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2025-01-03
AI Technical Summary
The prior art is difficult to simultaneously improve the optical and mechanical properties of transparent ceramics. Traditional methods such as high-temperature heat treatment and chemical vapor deposition processes may cause thermal stress and inhomogeneity when improving the mechanical properties, and are difficult to modify deeply.
The process of combining laser pretreatment (LPP) and laser impact enhancement (LSP) is adopted to accurately control the laser energy input, remove surface and deep defects, and improve the optical transmittance and crack propagation resistance of transparent ceramics.
It has achieved a comprehensive improvement in the optical and mechanical properties of transparent ceramics, enhanced the ability to resist laser damage and mechanical stability, and solved the problem that traditional methods are difficult to take into account both optical and mechanical properties.
Smart Images

Figure CN119241277A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of post-processing of optical materials, and in particular, relates to a laser modification method of transparent ceramics and the transparent ceramics thereof. Background Art
[0002] Transparent ceramics are advanced materials with high optical transmittance, excellent mechanical properties and chemical stability, and are widely used in high-energy laser systems, aerospace, military protective equipment and other high-performance optical components. For example, transparent ceramics such as magnesium aluminum spinel, yttrium aluminum garnet (YAG) and yttrium oxide have become ideal candidate materials for optical window materials, protective devices and laser equipment due to their good optical properties and mechanical strength.
[0003] However, with the increasing demand for high-energy lasers and extreme environments, there is an urgent need to improve the optical damage threshold (LIDT) and mechanical strength of transparent ceramics in these applications. Ceramic materials usually have microcracks and microscopic defects, which are easily enlarged under high-energy laser irradiation or mechanical impact, thereby reducing their optical and mechanical properties. Therefore, how to simultaneously improve the optical properties (such as transmittance, LIDT) and mechanical properties (such as fracture toughness, impact resistance) of transparent ceramics has become a technical problem that needs to be solved urgently.
[0004] Compared with other materials, transparent ceramics are more challenging in post-processing. Traditional mechanical processing, chemical treatment and heat treatment methods are usually unable to effectively improve microcracks in ceramics, but may cause uneven stress distribution on the surface and internal structure of the material. In contrast, laser processing technology, especially laser pretreatment (LPP) and laser shock strengthening (LSP), can precisely control the energy input and perform local or global processing on transparent ceramics in a non-contact manner, effectively improving the optical and mechanical properties of the material.
[0005] Laser pretreatment (LPP): This technology is mainly used to optimize the surface optical properties. It removes microscopic defects on the material surface and smoothes the surface roughness through precise laser energy input, thereby improving the optical transmittance and LIDT of transparent ceramics.
[0006] Laser shock processing (LSP): LSP uses high-energy laser pulses to induce high-pressure shock waves on the material surface, forming a deep compressive residual stress layer, which effectively improves the crack growth resistance and impact resistance of transparent ceramics.
[0007] Compared with other methods, laser technology has the following advantages:
[0008] 1. Precise control: Laser processing can precisely control energy input and processing depth, avoiding surface damage and microcrack propagation that may be caused by traditional heat treatment.
[0009] 2. Combination of surface and deep modification: The combination of LPP and LSP can not only improve the surface optical properties, but also improve the deep mechanical properties.
[0010] 3. Wide applicability: Laser technology is applicable to a variety of transparent ceramic materials and is not limited by the chemical composition and microstructure of the materials.
[0011] There are many deficiencies in the existing methods for post-treatment modification of transparent ceramics, such as:
[0012] "An easy-to-process high-performance ceramic substrate and its preparation method", invention authorization / publication number: CN117142842A. This patent proposes a method for improving the optical properties of transparent ceramics by high-temperature heat treatment, mainly by repairing microcracks and lattice defects through thermal diffusion. However, high-temperature treatment often easily induces new thermal stress, especially in large-size ceramic materials, and cannot effectively improve its mechanical properties, and the improvement of surface optical properties is limited. During the heat treatment process, the thermal stress release of transparent ceramics is uneven, which easily leads to the generation of new microscopic defects, and is not suitable for improving the impact resistance of transparent ceramics and the introduction of deep residual stress. Another invention patent "Methods for enhancing transparent ceramics and ceramics", invention authorization / publication CN109661384A. This patent describes a method for repairing surface defects of transparent ceramics by chemical vapor deposition (CVD) process. Although this method can effectively fill surface cracks, it has limited repair effect on deep defects and microcracks. At the same time, the process is complicated and it is difficult to achieve uniform mechanical property improvement. Chemical treatment is mainly aimed at surface modification, it is difficult to introduce deep compressive residual stress, and the deposited layer may affect the overall optical transmittance of the material.
[0013] In summary, most of the existing modification methods of transparent ceramics focus on surface treatment, which makes it difficult to simultaneously improve the optical and mechanical properties of the material. Laser processing technology, especially the combination of laser pretreatment (LPP) and laser shock strengthening (LSP), can not only effectively repair surface defects, but also introduce deep compressive residual stress, thereby comprehensively improving the comprehensive performance of transparent ceramics. Therefore, the use of laser processing technology for secondary modification of transparent ceramics has obvious necessity and advantages. Summary of the invention
[0014] The purpose of the present invention is to propose a laser modification method and process for optical and mechanical modification of transparent ceramics, so as to solve the current situation that there is a blank in the prior art for improving the optical and mechanical methods of transparent ceramics.
[0015] To achieve the above object, the technical solution of the present invention is achieved as follows:
[0016] A laser modification method for optical and mechanical modification of transparent ceramics. This invention patent proposes a process combining laser pretreatment (LPP) with laser shock strengthening (LSP) to improve the optical and mechanical properties of transparent ceramics. The process reasonably arranges the laser modification steps and sequentially performs surface and deep treatment to achieve secondary modification of transparent ceramic materials, thereby enhancing their laser damage resistance (LIDT) and mechanical stability. The process flow includes the following main steps:
[0017] S1. Sample preparation
[0018] First, the transparent ceramic sample to be processed is prepared, including cleaning and surface microscopic inspection to ensure that there is no obvious contamination or mechanical damage on the sample surface. According to the needs, the appropriate transparent ceramic material (such as magnesium aluminum spinel, YAG or yttrium oxide) is selected for subsequent laser processing steps.
[0019] S2. Laser Damage Threshold (LIDT) Test and Laser Shock Peening (LSP) Safety Threshold Test
[0020] Before LPP treatment, the LIDT of transparent ceramics needs to be determined, and laser pretreatment process should be carried out with laser energy density lower than LIDT, and damage threshold test should be carried out on the samples to evaluate their optical properties and surface damage behavior. The effect of LPP treatment on the transparency and anti-laser damage ability of the incident surface should be observed in particular.
[0021] Before LSP treatment, it is also necessary to clarify the safety threshold of laser impact strengthening of transparent ceramics. Subsequently, it is necessary to carry out laser shock strengthening process with laser energy density lower than the safety threshold, conduct damage threshold test on the sample, and evaluate the subsequent surface damage behavior.
[0022] S3. Laser Pretreatment Process (LPP)
[0023] Laser pretreatment (LPP) is performed on the incident surface of transparent ceramics to remove microscopic defects and cracks on the material surface, improve optical properties, and increase laser damage threshold (LIDT) and optical transmittance by precisely controlling laser energy density and pulse width.
[0024] S4. Optical and mechanical tests
[0025] Export results after optical and mechanical testing of samples1
[0026] S5. Laser shock peening (LSP) process
[0027] Laser shock peening is performed on the incident surface of the transparent ceramic, and the laser energy density and pulse width are precisely controlled to perform laser shock peening below the laser safety threshold obtained in the test of step S2 to improve mechanical properties.
[0028] S6. Optical and mechanical tests
[0029] Export results after optical and mechanical testing of samples2
[0030] S7. Evaluate whether test result 2 is better than result 1
[0031] If yes, the process is terminated, and the subsequent laser processing process adopts a solution of first performing laser pretreatment and then performing laser shock strengthening.
[0032] If not, prepare new samples to be processed and proceed to the subsequent process steps
[0033] S8. Laser shock peening (LSP) process
[0034] Laser shock peening is performed on the incident surface of the transparent ceramic, and the laser energy density and pulse width are precisely controlled to perform laser shock peening below the laser safety threshold obtained in the test of step S2 to improve mechanical properties.
[0035] S9. Optical and mechanical tests
[0036] Export results after optical and mechanical testing of samples3
[0037] S10. Laser Pretreatment Process (LPP)
[0038] Laser pretreatment (LPP) is performed on the incident surface of transparent ceramics to remove microscopic defects and cracks on the material surface, improve optical properties, and increase laser damage threshold (LIDT) and optical transmittance by precisely controlling laser energy density and pulse width.
[0039] S11. Optical and mechanical tests
[0040] Export results after optical and mechanical testing of samples4
[0041] S12. Evaluate whether test result 4 is better than result 3
[0042] If yes, the process is terminated, and the subsequent laser processing process adopts the scheme of first performing laser shock strengthening and then performing laser pretreatment process.
[0043] If not, further evaluate whether result 4 is better than result 3
[0044] S13. Evaluate whether result 4 is better than result 3
[0045] If yes, the process is terminated, and the subsequent laser processing process adopts the scheme of first performing laser shock strengthening and then performing laser pretreatment process.
[0046] If not, the process is terminated, and the subsequent laser processing process adopts a solution of first performing laser pretreatment and then performing laser shock strengthening process.
[0047] Through the above steps, the invention achieves all-round optimization of the optical and mechanical properties of transparent ceramics. Laser pretreatment improves the optical transmittance and laser damage threshold of the material, while laser shock strengthening enhances the material's resistance to mechanical damage and the introduction of deep residual compressive stress. This combined laser modification process can be widely used in the modification of transparent ceramics in high-performance optical components, laser shields, and other high-power laser systems.
[0048] Preferably, the optics involved in step S4, step S6, step S9 and step S11 include laser induced damage threshold, optical transmittance, optical absorptivity, bandgap width and surface roughness; the mechanical tests include Vickers hardness, fracture toughness, and flexural strength.
[0049] Preferably, in steps S3 and S10, the laser energy density used in the laser pre-treatment involved needs to be smaller than the LIDT measured in S2.
[0050] Preferably, in the steps S5 and S8, the laser energy density used in the laser shock strengthening is less than the safety threshold measured in S2.
[0051] Preferably, in steps S3 and S10, the laser spot setting range in the laser pretreatment process is 0.5-2 mm. 2 . The laser wavelength optional range includes: 1064nm, 532nm, 355nm.
[0052] Preferably, in step S2, the test method of the laser induced damage threshold is a 1-on-1 method in the international standard ISO21254.
[0053] Preferably, in steps S5 and S8, when laser shock strengthening transparent ceramics, the laser spot setting range is 0.5-2 mm 2 The laser wavelength options include: 1064nm, 532nm, 355nm and the energy density is adjustable.
[0054] Compared with the prior art, the present invention has the following beneficial effects:
[0055] 1. The dual laser modification process, the organic combination of laser pretreatment process and laser shock strengthening, has comprehensively improved the optical and mechanical properties of transparent ceramics.
[0056] 2. Dynamic adjustment of process sequence: according to test feedback, the process sequence of laser pretreatment followed by laser shock peening or laser shock peening followed by laser pretreatment can be flexibly selected to achieve the best modification effect.
[0057] 3. Maintaining or improving the optical properties of transparent ceramics while improving the mechanical properties solves the problem of balancing mechanical and optical properties in the existing technology. BRIEF DESCRIPTION OF THE DRAWINGS
[0058] Figure 1 This is a process flow diagram DETAILED DESCRIPTION
[0059] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and embodiments, but this should not limit the protection scope of the present invention.
[0060] Embodiment 1:
[0061] First, the magnesium-aluminum spinel transparent ceramic sample to be processed is prepared, including cleaning and surface microscopic inspection, to ensure that there is no obvious contamination or mechanical damage on the surface of the magnesium-aluminum spinel transparent ceramic. According to the needs, the appropriate magnesium-aluminum spinel transparent ceramic material is selected for the subsequent laser processing steps.
[0062] Before LPP treatment, the LIDT of magnesium-aluminum spinel transparent ceramics needs to be determined. After testing, the damage threshold of magnesium-aluminum spinel transparent ceramics is 11J / cm 2 . Use 9J / cm 2 The laser pretreatment process was carried out with a laser energy density of 1000 nm, and the damage threshold test was performed on the magnesium aluminum spinel transparent ceramic sample to evaluate its optical properties including transmittance, absorptivity and surface damage behavior. The effect of LPP treatment on the transparency of the incident surface and the ability to resist laser damage was observed in particular.
[0063] Before LSP treatment, it is also necessary to clarify the safety threshold of laser impact strengthening of magnesium-aluminum spinel transparent ceramics. The energy density of the safety threshold is 20J / cm 2 . Follow up with 18J / cm 2 The laser shock peening process was carried out with a laser energy density of 1000 nm, and mechanical tests (sample hardness, fracture toughness, and flexural strength) were performed on the samples to evaluate their subsequent surface damage behavior.
[0064] Laser pretreatment is performed on the incident surface of magnesium-aluminum spinel transparent ceramics. The laser energy density, scanning times and pulse width are precisely controlled. At this time, the laser energy density range is 7J / cm 2 , scan times 6J / cm 2The pulse width range is 11ns, which is designed to remove microscopic defects and cracks on the material surface, improve optical properties and increase laser damage threshold (LIDT) and optical transmittance.
[0065] The optical and mechanical tests of the magnesium aluminum spinel transparent ceramic sample were performed and the results were summarized and derived as result 1, which is: LIDT = 11.2 J / cm 2 , linear transmittance 81%@250nm, surface strength = 11.2Gpa, fracture toughness = 1.45Mpam 1 / 2 And flexural strength equal to 153N / mm 2 .
[0066] Laser shock peening is performed on the incident surface of magnesium-aluminum spinel transparent ceramics. By precisely controlling the laser energy density and pulse width, laser shock peening is performed below the laser safety threshold obtained by testing to improve mechanical properties.
[0067] The optical and mechanical tests of the magnesium aluminum spinel transparent ceramic sample were conducted and the results were recorded as result 2: LIDT = 11 J / cm 2 , linear transmittance 81%@250nm, surface strength = 10.8Gpa, fracture toughness = 1.35Mpam 1 / 2 And flexural strength equal to 143N / mm 2 .
[0068] Evaluate whether test result 2 is better than result 1
[0069] If the result is "No", prepare a new sample of magnesium aluminum spinel transparent ceramic to be processed and proceed to the subsequent process steps.
[0070] Laser shock peening was performed on the incident surface of magnesium-aluminum spinel transparent ceramics. The laser energy density was precisely controlled to 15 J / cm 2 With 6 scans, laser shock peening was performed below the laser safety threshold obtained by the test. Improved mechanical properties.
[0071] After optical and mechanical testing of the sample, the results are marked as 3, specifically: LIDT = 11.5 J / cm 2 , linear transmittance 82%@250nm, surface strength = 11.7Gpa, fracture toughness = 1.55Mpam 1 / 2 And flexural strength equal to 159N / mm 2 .
[0072] Laser pretreatment (LPP) is performed on the incident surface of magnesium aluminum spinel transparent ceramics to remove microscopic defects and cracks on the material surface by precisely controlling the laser energy density and pulse width, thereby improving the optical properties and increasing the laser damage threshold (LIDT) and optical transmittance.
[0073] After optical and mechanical testing of the sample, the results are exported and marked as result 4, which is: LIDT = 12.5 J / cm 2 , linear transmittance 82%@250nm, surface strength = 12.5Gpa, fracture toughness =
[0074] 1.75Mpam 1 / 2 And flexural strength equal to 179N / mm 2 .
[0075] Evaluate whether test result 4 is better than result 3
[0076] The result shows "yes", and the process is terminated. The subsequent laser processing process adopts the scheme of first performing laser shock strengthening and then performing laser pretreatment.
[0077] Through the above steps, the invention achieves all-round optimization of the optical and mechanical properties of transparent ceramics. Laser pretreatment improves the optical transmittance and laser damage threshold of the material, while laser shock strengthening enhances the material's resistance to mechanical damage and the introduction of deep residual compressive stress. This combined laser modification process can be widely used in the modification of transparent ceramics in high-performance optical components, laser shields, and other high-power laser systems.
[0078] Embodiment 2:
[0079] First, the yttrium oxide transparent ceramic sample to be processed is prepared, including cleaning and surface microscopic inspection, to ensure that there is no obvious contamination or mechanical damage on the surface of the yttrium oxide transparent ceramic. According to the needs, the appropriate yttrium oxide transparent ceramic material is selected for the subsequent laser processing steps.
[0080] Before LPP treatment, the LIDT of yttrium oxide transparent ceramics needs to be determined. After testing, the damage threshold of yttrium oxide transparent ceramics is 10J / cm 2 . Use 8J / cm 2 The laser pretreatment process was carried out with a laser energy density of 1000 nm, and the damage threshold test was performed on the yttrium oxide transparent ceramic samples to evaluate their optical properties including transmittance, absorptivity and surface damage behavior. The effect of LPP treatment on the transparency of the incident surface and the ability to resist laser damage was observed in particular.
[0081] Before LSP treatment, it is also necessary to clarify the safety threshold of laser impact strengthening of yttrium oxide transparent ceramics. The energy density of the safety threshold is 30J / cm 2 . Follow up with 28J / cm 2 The laser shock peening process was carried out with a laser energy density of 1000 nm, and mechanical tests (sample hardness, fracture toughness, and flexural strength) were performed on the samples to evaluate their subsequent surface damage behavior.
[0082] Laser pretreatment is performed on the incident surface of yttrium oxide transparent ceramics. The laser energy density, scanning times and pulse width are precisely controlled. At this time, the laser energy density range is 6J / cm 2 , scan times 5J / cm 2 The pulse width range is 9ns, which is designed to remove microscopic defects and cracks on the material surface, improve optical properties and increase laser damage threshold (LIDT) and optical transmittance.
[0083] After optical and mechanical tests on the yttrium oxide transparent ceramic sample, the results are summarized and derived as result 1. Result 1 is: LIDT = 9 J / cm 2 , linear transmittance 83%@250nm, surface strength = 9.3Gpa), fracture toughness = 1.2Mpam 1 / 2 And flexural strength equal to 157N / mm 2 .
[0084] Laser shock peening is performed on the incident surface of yttrium oxide transparent ceramics. By precisely controlling the laser energy density and pulse width, laser shock peening is performed below the laser safety threshold obtained by testing. This improves mechanical properties.
[0085] After optical and mechanical tests on the yttrium oxide transparent ceramic sample, the result 2 is derived and recorded as: LIDT = 8 J / cm 2 , linear transmittance 82%@250nm, surface strength = 8.9Gpa), fracture toughness = 1.0Mpam 1 / 2 And flexural strength equal to 142N / mm 2 .
[0086] Evaluate whether test result 2 is better than result 1
[0087] The results show that result 2 is not due to result 1, so a new yttrium oxide transparent ceramic sample to be processed is prepared and the subsequent process steps are carried out.
[0088] Laser shock peening treatment is performed on the incident surface of yttrium oxide transparent ceramics. The laser energy density is precisely controlled to 17J / cm 2 With 5 scans, laser shock peening was performed below the laser safety threshold obtained by the test. Improved mechanical properties.
[0089] The results of optical and mechanical tests on the sample are marked as 3, specifically: LIDT = 9.2 J / cm 2 , linear transmittance 83%@250nm, surface strength = 9.5Gpa), fracture toughness = 1.25Mpam 1 / 2 And flexural strength equal to 163N / mm 2 .
[0090] Laser pretreatment (LPP) is performed on the incident surface of yttrium oxide transparent ceramics to remove microscopic defects and cracks on the material surface, improve optical properties, and increase laser damage threshold (LIDT) and optical transmittance by precisely controlling laser energy density and pulse width.
[0091] After optical and mechanical testing of the sample, the results are exported and marked as result 4, specifically: LIDT = 9.4 J / cm 2 , linear transmittance 84% @ 250nm, surface strength = 9.7Gpa), fracture toughness = 1.28Mpam 1 / 2 And flexural strength equal to 168N / mm 2 .
[0092] Evaluate whether test result 4 is better than result 3
[0093] If the result is "yes", the process is terminated, and the subsequent laser treatment process adopts the scheme of first performing laser shock strengthening and then performing laser pretreatment.
[0094] Through the above steps, the invention achieves all-round optimization of the optical and mechanical properties of yttrium oxide transparent ceramics. Laser pretreatment improves the optical transmittance and laser damage threshold of the material, while laser shock strengthening enhances the mechanical damage resistance and deep residual compressive stress introduction of yttrium oxide transparent ceramic materials. This combined laser modification process can be widely used in the modification of transparent ceramics in high-performance optical components, laser protective covers and other high-power laser systems.
[0095] Embodiment three:
[0096] First, the YAG transparent ceramic sample to be processed is prepared, including cleaning and surface microscopic inspection, to ensure that there is no obvious contamination or mechanical damage on the surface of the YAG transparent ceramic. The appropriate YAG transparent ceramic material is selected according to the needs for the subsequent laser processing steps.
[0097] Before LPP treatment, the LIDT of YAG transparent ceramics needs to be determined. After testing, the damage threshold of YAG transparent ceramics is 7J / cm 2 . Use 6J / cm 2 The laser pretreatment process was carried out with a laser energy density of 1000 nm, and the damage threshold test was performed on the YAG transparent ceramic sample to evaluate its optical properties including transmittance, absorptivity and surface damage behavior. The effect of LPP treatment on the transparency of the incident surface and the ability to resist laser damage was observed in particular.
[0098] Before LSP treatment, it is also necessary to clarify the safety threshold of laser impact strengthening of YAG transparent ceramics. The energy density of the safety threshold is 25J / cm 2. Follow up with 23J / cm 2 The laser shock peening process was carried out with a laser energy density of 1000 nm, and mechanical tests (sample hardness, fracture toughness, and flexural strength) were performed on the samples to evaluate their subsequent surface damage behavior.
[0099] Laser pretreatment is performed on the incident surface of yttrium aluminum garnet transparent ceramics. The laser energy density, scanning times and pulse width are precisely controlled. At this time, the laser energy density range is 7J / cm 2 , scan times 8J / cm 2 The pulse width range is 9ns, which is designed to remove microscopic defects and cracks on the material surface, improve optical properties and increase laser damage threshold (LIDT) and optical transmittance.
[0100] After optical and mechanical tests on the YAG transparent ceramic sample, the results are summarized and recorded as Result 1: LIDT = 7.2 J / cm 2 , linear transmittance 81%@250nm, surface strength = 10.2Gpa, fracture toughness = 1.25Mpam 1 / 2 And flexural strength equal to 143N / mm 2 .
[0101] Laser shock peening is performed on the incident surface of yttrium aluminum garnet transparent ceramics. By precisely controlling the laser energy density and pulse width, laser shock peening is performed below the laser safety threshold obtained from the test. The mechanical properties are improved.
[0102] After optical and mechanical tests on the YAG transparent ceramic sample, the results recorded as Result 2 are as follows: LIDT = 7.5 J / cm 2 , linear transmittance 83%@250nm, surface strength = 11.2Gpa, fracture toughness =
[0103] 1.35Mpam 1 / 2 And flexural strength equal to 149N / mm 2 .
[0104] Evaluate whether test result 2 is better than result 1
[0105] If the result is "yes", the process is terminated, and the subsequent laser processing process adopts the scheme of first performing laser pretreatment and then laser shock strengthening.
[0106] Through the above steps, the invention achieves all-round optimization of the optical and mechanical properties of yttrium aluminum garnet transparent ceramics. Laser pretreatment improves the optical transmittance and laser damage threshold of yttrium aluminum garnet materials, while laser shock strengthening enhances the mechanical damage resistance and deep residual compressive stress introduction of yttrium aluminum garnet transparent ceramic materials. This combined laser modification process can be widely used in the modification of transparent ceramics in high-performance optical components, laser protective covers and other high-power laser systems.
Claims
1. A laser modification method for transparent ceramics, characterized in that: The method combines the laser pretreatment process (LPP) with the laser shock peening process (LSP) to improve the optical and mechanical properties of transparent ceramics, and specifically includes the following steps: S1. Sample preparation: cleaning and inspecting the surface of the transparent ceramic sample to be processed to ensure that it is free of contamination or mechanical damage, wherein the transparent ceramic is selected from magnesium aluminum spinel, yttrium aluminum garnet (YAG), yttrium oxide or a mixture thereof; S2. Laser Damage Threshold (LIDT) Test and Laser Shock Peening (LSP) Safety Threshold Test: LIDT test and LSP safety threshold test were performed on transparent ceramic samples respectively to ensure that the laser energy density during processing is below these thresholds to avoid irreversible damage; S3. Laser pretreatment process (LPP): LPP is performed on the incident surface of transparent ceramics to remove surface microscopic defects and improve optical transmittance and laser damage threshold (LIDT) by controlling laser energy density and pulse width; S4. Preliminary optical and mechanical tests: Conduct comprehensive tests on the optical and mechanical properties of the transparent ceramic samples after LPP treatment, and record them as test result 1; S5. Laser shock peening (LSP): By controlling the laser energy density and pulse width, LSP is performed on the incident surface of the transparent ceramic sample below the safety threshold to introduce deep compressive residual stress and enhance the crack propagation resistance and impact resistance. S6. Secondary test: The optical and mechanical properties of the transparent ceramic sample after LSP treatment are tested again in step S4, and the result is recorded as test result 2; S7. Result evaluation and process optimization: Compare test result 1 and test result 2. If test result 2 is better than test result 1, end the process and determine the order of LPP and then LSP. If test result 2 is not better than test result 1, adjust the LSP parameters and perform laser shock peening again. The order of LPP and LSP can be adjusted as needed to obtain the best optical and mechanical properties.
2. The laser modification method according to claim 1, characterized in that: The optical performance tests in steps S4 and S6 include LIDT, optical transmittance, absorptivity, bandgap and surface roughness tests, and the mechanical performance tests include Vickers hardness, fracture toughness and flexural strength tests.
3. The laser modification method according to claim 1, characterized in that: The laser energy density used in the laser pretreatment in step S3 is less than the LIDT measured in step S2.
4. The laser modification method according to claim 3, characterized in that: The laser energy density of the laser pretreatment is in the range of 2-9 J / cm 2 , the scanning times are 1-9 times, and the pulse width range is 8-12ns.
5. The laser modification method according to claim 1, characterized in that: The laser energy density used in the laser shock peening in step S5 is less than the safety threshold measured in step S2.
6. The laser modification method according to claim 5, characterized in that: The laser energy density of the laser shock peening is lower than the laser safety threshold obtained by testing, and the specific range is 5-18J / cm 2 , the number of scans is 2-8 times.
7. The laser modification method according to claim 1, characterized in that: After the LPP process, the improvement in optical performance was verified by LIDT testing, and the laser parameters were adjusted so that the LSP process did not affect the already improved optical performance.
8. A transparent ceramic treated by the laser modification method according to any one of claims 1 to 4, characterized in that: With optical and mechanical properties, including laser-induced damage threshold (10J / cm2-20J / cm 2 ), linear transmittance (≥80%), surface strength (≥9Gpa), fracture toughness (≥1.0Mpam 1 / 2 ) and flexural strength (≥140N / mm 2 ).
9. The transparent ceramic treated by the laser modification method according to claim 8, characterized in that: The transparent ceramic can be widely used in transparent ceramic modification in high-performance optical elements, laser protective covers and other high-power laser systems.
Citation Information
Patent Citations
Method for reinforcing transparent ceramics, and ceramic
CN109661384A
Easily-processed high-performance ceramic substrate and preparation method thereof
CN117142842A